Fabrication of nanoelectrode ensembles by electrodepositon of Au nanoparticles on single-layer graphene oxide sheets - Wang, Zhijuan (2013)
Nanoelectrode ensembles (NEEs) have been fabricated by the electrodeposition of Au nanoparticles (AuNPs) on single-layer graphene oxide (GO) sheets coated on a glassy carbon electrode (GCE). The fabricated NEEs show a typical sigmoidal shaped voltammetric profile, arising from the low coverage density of AuNPs on GCE and large distance among them, which can be easily controlled by varying the electrodeposition time. As a proof of concept, after the probe HS-DNA is immobilized on the NEEs through the Au–S bonding, the target DNA is detected with the methylene blue intercalator. Our results show that the target DNA can be detected as low as 100 fM, i.e. 0.5 amol DNA in 5 μL solution.